Frontispiece: Cross‐Linked Polymers as Scaffolds for the Low‐Temperature Preparation of Nanostructured Metal Oxides. Issue 42 (27th July 2020) - Centomo, Paolo; Zecca, Marco; Biffis, Andrea
Abstract : The current state of the art of the use of cross‐linked organic polymers, both insoluble (resins or gels) and soluble (micro‐ and nanogels), as aids for the low‐temperature preparation of stable metal oxide nanoparticles or nanostructured metal oxides is reviewed herein. Synthetic strategies for inorganic oxide nanomaterials of this kind can greatly benefit from the use of cross‐linked polymers, which may act as scaffolds/exotemplates during inorganic nanoparticle synthesis, or as stabilizers following post‐synthetic modification of the nanoparticles. For more information, see the Review by P. Centomo et al. on page 9243 ff.